Translation and Bilingualism in Monica Ali’s and Jhumpa Lahiri’s Marginalized Identities - Rizzo, Alessandra (Text Matters: A Journal of Literature, Theory and Culture, 2012)
This study, drawing upon contemporary theories in the field of migration, postcolonialism, and translation, offers an analysis of literary works by Monica Ali (of Bangladeshi origins) and Jhumpa Lahiri (of Bengali Indian parents). Ali and Lahiri epitomize second-generation immigrant literature, play with the linguistic concept of translating and interpreting as forms of hybrid connections, and are significant examples of how a text may become a space where multi-faceted identities co-habit in a process of deconstructing and reconstructing their own sense of emplacement in non-native places. Each immigrant text becomes a hybrid site, where second- and third generations of immigrant subjects move as mobile, fluctuating and impermanent identities, caught up in the act of transmitting their bicultural and bilingual experience through the use of the English language as their instrument of communication in a universe which tends to marginalize them. This investigation seeks to demonstrate how Ali and Lahiri represent two different migrant experiences, Muslim and Indian, each of which functioning within a multicultural Anglo-American context. Each text is transformed into the lieu where identities become both identities-intranslation and translated identities and each text itself may be looked at as the site of preservation of native identities but also of the assimilation (or adaptation) of identity. Second-generation immigrant women writers become the interpreters of the old and new cultures, the translators of their own local cultures in a space of transition.